The Canonization Process of the Masoretic Text - Sipilä, Seppo (The Bible translator, 2016)
This article discusses the process that gave canonical status to the Masoretic Text. The discussion will start from the present reality and continue backwards. Because the Masoretic Text is a creation of rabbinic Judaism and because the rabbis did discuss the status of various books within the Masoretic Text, this article will argue for a late dating both of the text as a collection and of its canonization. However, within Christian canons, the Masoretic Text acts as a canonical text in a limited way, in the sense that it is only a part of those canons. Besides, there is no moment in history where any authority declared the Masoretic Text canonical. Therefore, it is nowadays widely accepted as a canonical text, but without authorization.